Mathematic modeling of the influence of femur malalignment on the bearing of lower extremity joints - Korzh, Mykola; Romanenko, Konstantin; Karpinsky, Mykhaylo; Prozorovsky, Dmytro; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The forming of posttraumatic deformity of long bones is accompanied with development of secondary changes in all tissues of injured segment. Theoretically the redistribution of bearing areas, osteoarthritic changes and restriction of range of motion in adjusted joints can appear. Usage of mathematical modeling allows creating 3D models of biological objects and reveals main tendencies of the changes of their stress-strain status. The goal: to work out the mathematical model of lower extremity and to study, using the model, the influence of varus extraarticular deformity of femur on stress distribution in knee, ankle and subtallar joints. Methods: mathematical models of lower extremity under normal conditions and under conditions of femur varus deformity (45°) in middle 1/3. Exertion according to Mises was a criterion to assess stress-strain status. The modeling was performed using the system of automated designing SolidWorks and calculation of stress-strain status – program complex CosmosM. Results: in knee medial condyle of femur appeared more overloaded under the conditions of femur varus malalignment and corresponding area of bearing of proximal tibia (26.9 vs 4.9 MPa under normal conditions). Double increase in strain was observed on lateral edge of knee joint (6.1 vs 3.4 Mpa). On the level of ankle joint almost triple increase in stress-strain status was observed on lateral parts of both tibia and talar. Conclusion: varus malalignment of femur provokes severe increase in tension in femur and tibia, imbalance in tension significance on medial and lateral sides of these bones with its prevalence on medial side, and severe increase in tension value on medial side of bearing areas of knee joint.